Investigating short-term earthquake precursors detection through monitoring of total electron content variation in ionosphere - Zulhamidi, Nur Fatin Irdina; Abdullah, Mardina; Abdul Hamid, Nurul Shazana; Yusof, Khairul Adib; Bahari, Siti Aminah (Frontiers in Astronomy and Space Sciences, 2023)
The effectiveness and accuracy of earthquake precursors are measured by the ability of the precursors to predict the time, epicentral distance, and magnitude of the earthquake for short-term earthquake prediction. Past articles were reviewed to examine various studies of short-term earthquake precursor detection, particularly those that involved monitoring variations in total electron content (TEC). In this review, we examine recent studies that explore the use of the TEC parameter in the Lithospheric-Atmospheric-Ionospheric (LAI) interaction to forecast earthquake characteristics, including detection time, epicentral distance, and magnitude. This review characterizes anomalous observations of TEC parameters that may be linked to subsequent seismic events and investigates their correlation with earthquake properties. It has been conclusively demonstrated that TEC parameters show significant variations prior to earthquakes, and these results can be used in combination with other parameters to forecast earthquake properties.